Comparative efficacy of venous thromboembolism prophylaxis in patients with blunt trauma: Direct thrombin inhibitors vs low-molecular-weight heparin - Jen-Fu Huang; Chih-Po Hsu; Sheng-Yu Chan; Ya-Chiao Lin; Chi-Tung Cheng; Po-Cheng Lo; Meng-Hsuan Lee; Wen-Ching Weng; Yi-Jung Chen; Hsi-Hsin Li; Ken-Hsiung Chen; Shih-Tien Wang; et al. (Asian Journal of Surgery)
Background/objective: Venous thromboembolism (VTE) includes deep vein thrombosis (DVT) and pulmonary embolism (PE) and poses a risk to patients with trauma. This study compared the efficacy of direct thrombin inhibitors (DTIs) and low-molecular-weight heparin (LMWH) for the prophylaxis of VTE in patients with blunt injuries. Methods: This study analyzed data from the American College of Surgeons Trauma Quality Improvement Program, focusing on patients with an injury severity score (ISS) of ≥10 who received VTE prophylaxis. It identified covariates associated with VTE and adverse events. Results: Among 194,154 patients, those on DTIs (n = 205) were older and had higher ISS than those on LMWH (n = 193,949). The DTI group had higher rates of DVT (4.9 % vs 1.3 %), PE (3.4 % vs 0.7 %), unplanned visiting to the operating room (OR) (5.4 % vs 1.5 %), and mortality (8.8 % vs 2.5 %). After propensity score matching, DTIs were associated with increased incidences of DVT (4.9 % vs 1.8 %), PE (3.4 % vs 0.8 %), and unplanned visiting to the OR (5.4 % vs 1.5 %). Multivariate analysis indicated that DTIs significantly increased the odds of DVT (odds ratio, 2.945), PE (odds ratio, 4.250), and unplanned visiting to the OR (odds ratio, 4.175). Conclusion: DTIs are linked to more DVT and PE than LMWH in VTE prevention. LMWH is more effective than the other options and causes fewer adverse events. LMWH is preferred for patients with blunt injuries and an ISS of ≥10.